2017
DOI: 10.3846/16486897.2017.1307202
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biochar on Plant Diseases: What Should We Learn While Designing Biochar Substrates?

Abstract: The increasing demand for soilless substrates and rising environmental concerns about the use of non-renewable resources such as peat has led to the search for alternative constituents of growing mixtures for containerized plants. In this report we reviewed the works concerning biochar as constituent of growing media, targeting its influence on plant growth and plant disease. Biochar mostly has positive or neutral influences on plant growth compared with peat media when present in concentrations higher than 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 55 publications
4
55
0
2
Order By: Relevance
“…Plants inoculated with P. cinnamomi developed root rot, regardless of whether the soil was amended with biochar or biocharbokashi. Other studies have reported that soil pathogens, such as Phytophthora sp., were suppressed by low concentrations of biochar in the soil, but higher concentrations were ineffective or, in some cases, accelerated plant disease (Copley et al, 2015;Frenkel et al, 2017;Jaiswal et al, 2015;Zwart and Kim, 2012). Perhaps the rates of biochar used in the present study were too high to suppress development of P. cinnamomi in highbush blueberry.…”
Section: Discussionmentioning
confidence: 65%
“…Plants inoculated with P. cinnamomi developed root rot, regardless of whether the soil was amended with biochar or biocharbokashi. Other studies have reported that soil pathogens, such as Phytophthora sp., were suppressed by low concentrations of biochar in the soil, but higher concentrations were ineffective or, in some cases, accelerated plant disease (Copley et al, 2015;Frenkel et al, 2017;Jaiswal et al, 2015;Zwart and Kim, 2012). Perhaps the rates of biochar used in the present study were too high to suppress development of P. cinnamomi in highbush blueberry.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, biochar treated‐soil had raised pH and reduced chlorophyll content and soil available N. In a greenhouse experiment, Gu et al () concluded that biochar was efficient in reducing the bacterial wilt of tomato ( Ralstonia solanacearum ) by increasing chemotataxis ability of pathogen and suppressing the pathogen swarming mobility and root colonization. Moreover, recently a review study investigated that low amount of biochar (<1%) is considered effective in suppressing several plant diseases; but a higher rate of biochar (>3%), in most cases, is not effective or persuade plant diseases (Frenkel et al, ). Rogovska, Laird, Leandro, and Aller () indicated that two out of eight biochars significantly inhibited the severity of soybean root rot caused by Fusarium virguliforme under a greenhouse study, and further elucidated that suppression of root rot disease was not linked to the soil physico–chemical properties such as pH, bulk density, and soil moisture.…”
Section: Biochar As Soil Amelioratormentioning
confidence: 99%
“…To date, a biochar‐mediated influence has been shown for 15 different pathogens (fungi, oomycetes and nematodes) in 30 different pathosystems (i.e. plant/pathogen system) . The vast majority of these studied systems, however, have been small‐scale pot experiments.…”
Section: Introductionmentioning
confidence: 99%
“…plant/pathogen system). 27 The vast majority of these studied systems, however, have been small-scale pot experiments. The current study aims to test the influence of various biochars on the growth and disease resistance of Capsicum annuum L. (sweet pepper) under modern, high input, high yield, intensive net house cultivation over the course of several years (2011)(2012)(2013)(2014).…”
Section: Introductionmentioning
confidence: 99%